2004
DOI: 10.1038/sj.gt.3302292
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of gene delivery by genetic modification of adenovirus serotype 5 fibers and cell-selective transcriptional control

Abstract: Adenovirus (Ad)-mediated gene delivery is a promising approach for genetic manipulation of the vasculature and is being used in both preclinical models and clinical trials. However, safety concerns relating to infection of nontarget tissue and the poor infectivity of vascular cells compared to other cell types necessitates Ad vector refinement. Here, we combine a transductional targeting approach to improve vascular cell infectivity through RGD peptide insertion into adenovirus fibers, combined with transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Consistent with reports by others, 1719 our experimental data provide evidence of relatively high levels of VEGFR-1 promoter activity in blood vessel endothelial cells and in certain established glioma cell lines. The results of in vitro studies demonstrate direct correlation of VEGFR-1 promoter activity with levels of VEGF-stimulated migration and proliferation of glioma cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with reports by others, 1719 our experimental data provide evidence of relatively high levels of VEGFR-1 promoter activity in blood vessel endothelial cells and in certain established glioma cell lines. The results of in vitro studies demonstrate direct correlation of VEGFR-1 promoter activity with levels of VEGF-stimulated migration and proliferation of glioma cells.…”
Section: Discussionsupporting
confidence: 92%
“…The rationale behind the design of this vector is based on the following observations: (1) the utilization of retargeted CRAd by expression of RGD in the fiber knob improves vector transduction; 15,16 (2) the employment of the VEGFR-1/flt-1 promoter restricts CRAd replication to cancer cells and tumor-associated microvessels overexpressing VEGF; 1719 and (3) IL-24 selectively induces apoptosis in malignant cells and inhibits angiogenic activity. 2022 We investigated whether a combination of CRAdRGDflt-IL24-mediated oncolytic virotherapy and chemotherapy using temozolomide (TMZ) produces increased cytotoxicity against human glioma cells in comparison with these agents alone.…”
Section: Introductionmentioning
confidence: 99%
“…Such strategies can be applied to a wide range of tissue types and are not limited to malignant tissue. For example, inserted promoters have included the neuronal-specific neuron-specific enolase (NSE) promoter, the astrocyte-specific glial fibrillary acidic protein (GFAP) promoter [102], an alveolar epithelial type II cell-specific promoter, surfactant protein C (SP-C) promoter [103], and for transcriptional targeting in vascular tissue or endothelial cells, the intercellular adhesion molecule-2 (ICAM-2) or fms-like tyrosine kinase receptor-1 (FLT-1) promoters [104,105]. Achieving targeted transgene expression through the use of CRAds is a broad field and will therefore not be discussed further in this review article, as we will focus on transductional retargeting strategies.…”
Section: Retargeting Adenoviral Vectorsmentioning
confidence: 99%
“…Similarly, RGD-peptide modified adenovirus vector expressing a transgene under the control of the fms-like tyrosine kinase receptor (FLT-1) was shown to specifically target tumor endothelial cells demonstrating the feasibility of the modified adenoviral vector to target tumor vasculature that express very high levels of alpha (v) beta3-integrin. 137 Apart from adenoviral vector, RGD-peptide when attached to the surface of liposomes and injected in vivo was shown to target activated platelets and suggested to be a potential vascular drug or gene delivery system. 138 In vitro studies from our laboratory showed that cells treated with mixture of cyclic-RGD peptide and liposome enhanced transgene expression ( Fig.…”
Section: Tumor Targeting and Gene Transductionmentioning
confidence: 99%